2004
DOI: 10.1007/s10038-004-0208-6
|View full text |Cite
|
Sign up to set email alerts
|

Population prevalence of APOE, APOC3 and PPAR-α mutations associated to hypertriglyceridemia in French Canadians

Abstract: Hypertriglyceridemia (HTG) is known as a common metabolic disorder associated with increased production, decrease catabolism and/or decreased hepatic uptake of triglyceride (TG)-rich particles. We assessed, in the Que´bec City population, the allele frequency and haplotype distributions of mutations in genes related to HTG, such as the apolipoprotein E (APOE) (C112R and C158R), the apolipoprotein CIII (APOC3) (C-482T and C3238G) and the peroxisome proliferator-activated receptor alpha (PPARa) (L162V) genes. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…ApoCIII is a non-competitive LPL inhibitor, and ApoCIII gene polymorphisms can prevent an insulin effect on ApoCIII gene promoter, resulting in inappropriate LPL inhibition and increased plasma TG levels (Talmud and Humphries 1997). In the control group, the -482C > T and 3238C > G allele frequencies were similar to what was recently reported in French Canadians, with the -482C > T frequency being lower than in many other Caucasian populations (Garenc et al 2004). Interestingly, we found more cases of GH carrying the dyslipidemia-associated allele at both loci (-482T allele carriers, OR = 1.7; 3238G allele carriers, OR = 1.6), suggesting that women homozygous for both frequent ''protecting'' -482CC/ 3238CC ApoCIII genotypes were less susceptible to GH.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…ApoCIII is a non-competitive LPL inhibitor, and ApoCIII gene polymorphisms can prevent an insulin effect on ApoCIII gene promoter, resulting in inappropriate LPL inhibition and increased plasma TG levels (Talmud and Humphries 1997). In the control group, the -482C > T and 3238C > G allele frequencies were similar to what was recently reported in French Canadians, with the -482C > T frequency being lower than in many other Caucasian populations (Garenc et al 2004). Interestingly, we found more cases of GH carrying the dyslipidemia-associated allele at both loci (-482T allele carriers, OR = 1.7; 3238G allele carriers, OR = 1.6), suggesting that women homozygous for both frequent ''protecting'' -482CC/ 3238CC ApoCIII genotypes were less susceptible to GH.…”
Section: Discussionsupporting
confidence: 72%
“…It is also noteworthy that the ApoCIII -482C > T and 3238C > G polymorphisms were in strong linkage disequilibrium (D' = 0.89; P < 0.0001), as was recently observed in French Canadians (D' = 0.80; P < 0.0001) (Garenc et al 2004). In the present study, the frequency of ApoCIII -482C > T and 3238C > G double heterozygotes was about 2.5-fold higher than expected (15.5% vs. 6.7%; Table 3).…”
Section: Discussionsupporting
confidence: 68%
“…Genotyping was performed in the Laboratory for Molecular Genetics (Department of Biology and Medical Genetics, School of Medicine, Rijeka) by polymerase chain reaction/restriction fragment length polymorphism analysis using protocol previously described [24].…”
Section: Genotypingmentioning
confidence: 99%
“…Interestingly, the frequency of the S2 genotype seems to be more prevalent in LPL P207L-deficient patients from the present study than in a random population representing the metropolitan Québec City area. 23 However, it is not obvious to consider that patients bearing the LPL P207L mutation as well as the APOC3 S2 allele are those exhibiting a high lipid profile alteration that conduct them to the lipid clinic and this should be one raison that may explain the high APOC3 S2 allele frequency observed in LPL P20L patients. In the present study, the most intriguing results were observed with VLDL particles.…”
Section: Apoc3 Sst I Snp In Lpl-deficient Patientsmentioning
confidence: 99%